Răspuns :
(1) 7a+3b=3700
(2) a=8b+6
b=6c+8
---------------
Din (1) si (2) avem 7(8b+6) + 3b = 3700
56b+3b + 42 = 3700
59b= 3658
b= 3658:59 = 62
a= 8*62 + 6 = 496+6 = 502
c= b-8 / 6 = 62-8 / 6 = 54/6 = 9
---------------------------------------
(a-3b-35c)^2018 = (502 - 3*62 - 35*9)^2018 = (502-186-315)^2018 =
(502-501)^2018 = 1^2018 = 1.
(2) a=8b+6
b=6c+8
---------------
Din (1) si (2) avem 7(8b+6) + 3b = 3700
56b+3b + 42 = 3700
59b= 3658
b= 3658:59 = 62
a= 8*62 + 6 = 496+6 = 502
c= b-8 / 6 = 62-8 / 6 = 54/6 = 9
---------------------------------------
(a-3b-35c)^2018 = (502 - 3*62 - 35*9)^2018 = (502-186-315)^2018 =
(502-501)^2018 = 1^2018 = 1.